The Impact of Subclinical Hypothyroidism on Adverse Perinatal Outcomes and the Role of Thyroid Screening in Pregnancy - Wu, Mei-Qin; Liu, Jin; Wang, Ya-Qian; Yang, Ying; Yan, Chong-Huai; Hua, Jing (Frontiers in Endocrinology, 2019)
Subclinical hypothyroidism (SCH), a mild form of hypothyroidism, is a common disease among women of childbearing age. The impact of SCH on late adverse perinatal outcomes is unclear, and universal screening for thyroid function before or during pregnancy is also a key debate in thyroidology. In the present retrospective cohort study of 7587 women participating in Shanghai, we assessed whether SCH was associated with subsequent adverse perinatal outcomes and the relationship between the occurrence of late perinatal outcomes and the SCH screening time. Results show SCH was only associated with hypertensive disorders of pregnancy (HDP). Screening thyroid function in the first or second trimester in pregnancy correlated with HDP (odds ratio (OR) 9.69; 95% confidence interval (CI) 1.73-54.48 and OR 3.66; 95% CI 1.07-12.57, respectively), while there was not significant relationship between preconception thyroid function screening and HDP. To some extent, SCH during pregnancy is associated with late HDP, and preconception thyroid function screening may reduce the incidence of HDP caused by SCH.